Retrospective demographic study on tooth impaction in a Malaysian sample - Kashmoola, Muhannad Ali; Mustafa, Nazih Shaban; Abdul Qader, Omar Abdul Jabbar; Jamaluddin, Siti Aminah (University of Dicle, 2019)
Failure of tooth to erupt into the dental arch within expected time is referred to as impaction. The most common reasons for tooth impaction include tooth follicle displacement, impaction due to crowding, tooth may be missing and infrequent extraction of lower first and second molar. Other reasons include retention or premature loss of deciduous teeth and other causes. The most commonly affected teeth are the lower third molars, maxillary canines, maxillary second premolars and supernumerary teeth. The aim of this study was to determine the prevalence of impacted tooth through Orthopanthomograph (OPG) images among patients attending the Polyclinic Faculty of Dentistry (FOD), IIUM Kuantan Campus. A retrospective study was carried using OPG images. Of the 2722 OPG images, 1248 OPGs that fulfilled the inclusion criteria which were taken from patients who attended at Polyclinic of FOD from 1st April 2009 until 31st May 2012. Then, it was classified into the types of tooth impaction according to their age, gender and race. All the collected data has been analyzed using SPSS Version 20.0. Of the 1248 OPG images selected, the total OPGs with tooth impaction were 528. The most common impacted tooth was mandibular third molar (68%), followed by maxillary third molar (26%), maxillary canine (1.8%), mandibular supernumerary tooth (0.9%) and mandibular second premolar (0.7%). The tooth impaction also had significant differences (p<0.05) regarding to age, sex and race. The cases more common in age group of 18 to 24 years old (57%) and female (66%) population. Prevalence of impacted tooth cases is relatively high in Polyclinic Faculty of Dentistry, IIUM Kuantan Campus that needs to be diagnosed as soon as possible. We hope this study may help students and clinicians in managing or planning treatment in early detection and prevention.